The Influence of the Realistic Mathematics Approach (RME) on Fifth Grade Students’ Mathematics Learning Outcomes and Critical Thinking Abilities - Tantri, Risa; Gusrita, Silvia; Sakti, Faradiela; Susanti, Tuti; Farhan, Trianda (Journal Of Teaching And Learning In Elementary Education, 2024)
The importance of implementing innovative learning models, such as the realistic mathematics approach (RME), is a solution to improve student interaction and mathematics learning outcomes. This research aims to evaluate the effect of the Realistic Mathematics (RME) approach on Mathematics learning outcomes and critical thinking abilities of students in classes VA and VB at SDN 02 Percontohan Bukittingi. The research method used was a quasi-experimental research design (Quasi Experiment) with an experimental group of 25 students at VA SDN 02 Percontohan Bukittingi (class with the PMR approach) and a control group of 24 students at VB SDN 02 Percontohan Bukittingi (class with conventional learning). The research instrument involved critical thinking ability tests and Mathematics learning outcomes tests (Pre-test and Post-test). The results of data analysis show that the application of the Realistic Mathematics Approach has a significant influence in improving Mathematics learning outcomes and students' critical thinking abilities (Sig. 0.00 < 0.05). The experimental group showed a higher increase in average scores. (83.68) compared to the control group (61.54). The Realistic Mathematics Approach Model can be used as an effective alternative for teachers to improve student's critical thinking skills and understanding of mathematical concepts.